Pengaruh Faktor Individu dan Faktor Lingkungan Organisasi Terhadap Kinerja Pegawai - Hanifa Djakaria; Rahmat Laan; Fauziyah Lamaya (Program Studi Manajemen - Fakultas Ekonomi - Universitas Muhammadiyah Kupang, 2019)
This study aims to analyze the influence of individual factors andorganizational environmental factors both simultaneously andpartially on the performance of KPPN Waingapu employees. Theresearch sample amounted to 28 people. Determination of the sampleusing the saturated sample technique. The main instrument of datacollection is a questionnaire. Data were analyzed using multipleregression techniques. The results showed that simultaneous andpartial individual factors and work environment significantlyinfluence employee performance.